Developing an intrauterine device self-removal guide: a mixed methods qualitative and small pilot study - Francesca Collins; Kelly Gilmore; Kelsey A. Petrie; Lyndsey S. Benson (BMC, 2022)
Abstract Background The intrauterine device (IUD) is a highly effective form of long-acting reversible contraception (LARC) with few contraindications. Users, however, often encounter barriers to desired removal. IUD self-removal may mitigate these obstacles. We sought to develop a guide for IUD self-removal with the aim of increasing user control over the method. Methods This was a two-phase mixed-methods qualitative and small pilot study with the aim of developing an IUD self-removal guide. We conducted an online content analysis of advice for IUD self-removal as well as interviews with expert key informants to develop an IUD self-removal guide. We next recruited IUD-users who had previously attempted self-removal to participate in focus group discussion and individual interviews to further refine the guide. In the second phase of the study, we piloted the guide among eight IUD-users seeking removal interested in attempting self-removal. Results Expert key informants agreed that IUD self-removal was safe and low risk. The primary components of successful IUD self-removal elicited were ability to feel and grasp the strings, a crouched down position, and multiple attempts. A preference for presenting IUD self-removal as safe was emphasized. In the second phase, participants in the clinical pilot suggested more information for non-palpable strings, but liked the style and information provided. One participant successfully removed their IUD. Conclusions IUD-users reported satisfaction with our guide. In our small pilot, the majority were unable to remove their own IUD. A larger study is needed to assess acceptability, feasibility, and efficacy in increasing successful self-removal.